Synthesis and Pharmacological Evaluation of 2-(4-Halosubstituted phenyl)-4,5-diphenyl-1H-imidazoles - G. Nagalakshmi (E-Journal of Chemistry)
In the present study, 2-(4-halosubstituted phenyl)-4,5-diphenyl-1Himidazoles have been synthesized by refluxing benzil and ammonium acetate with different 4-halosubstituted aromatic aldehydes in glacial acetic acid. The structural assignment of this compound has been made on the basis of elemental analysis, UV, IR, 1H NMR and Mass spectral data. Toxicity of the compound has been determined. The synthesized compound was evaluated for antiinflammatory activity against carrageenan induced paw oedema and anticonvulsant activity against maximal electro-shock-induced convulsions in rats.